Analisis Praktikalitas Modul Fisika Mengintegrasikan Kemampuan Berpikir Kreatif Pada Materi Hukum Newton - Hufri Hufri; Sintia Sintia; Sri Indrawati Prihatin Ningsih (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
This research is motivated by the low creativity of students' thinking in learning and teaching materials in schools have not fully facilitated students' creative thinking abilities. Creative thinking is very much needed in learning, therefore supporting teaching materials are needed that can facilitate students' creative thinking skills, one of which is a module. For this reason, researchers will develop a Physics module that integrates creative thinking skills in it. This study aims to determine the practicality of the Physics module developed on Newton's law material. This type of research is included in research and development or commonly called R&D research. The research model with the ADDIE step is the model used in this study. The reason for choosing this model is that this model is suitable for module development because each stage carries out an evaluation so as to minimize product errors. for data collection in this study used a practicality test questionnaire that had previously been validated. This practicality test questionnaire was filled out by practitioners consisting of three teachers and 30 students. The data analysis technique uses a practical analysis of the module which is weighted using a Likert scale. The average practicality value of the Physics module by teachers and students who integrate students' creative thinking skills into Newton's law material is 86% and 91% with very practical criteria so that it can be stated that the Physics module has high practicality and can be used in learning.